2017
DOI: 10.1002/app.46010
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic properties of some bis‐chalcone derivatives‐based nanofibers

Abstract: Two bis-chalcone derivatives, (2E,6E)-2,6-bis[(thiophen-2-yl)methylene]cyclohexanone (C1) and (2E,6E)-2,6-bis[(furan-2yl)methylene]cyclohexanone (C2)-based electrochromic (EC) nanofibers were produced in the presence of poly(methyl methacrylate) (PMMA) as supporting polymer using the electrospinning technique. The scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy were used to examine morphology and chemical compositions of nanofibers before and after stability test. SEM images of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…This redox process showed that the electrochemical behaviors of P1 and P2 are reversible up to 200 mV/s. In addition, for both examples, the linearity of the plots shows that the electrochemical process can be controlled by the diffusion step at scan rates lower than 200 mV/s (Erasmus, 2011;Yellepa and Mallapa, 2015;Nohut Maşlakcı et al, 2018).…”
Section: Electrochemical Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This redox process showed that the electrochemical behaviors of P1 and P2 are reversible up to 200 mV/s. In addition, for both examples, the linearity of the plots shows that the electrochemical process can be controlled by the diffusion step at scan rates lower than 200 mV/s (Erasmus, 2011;Yellepa and Mallapa, 2015;Nohut Maşlakcı et al, 2018).…”
Section: Electrochemical Resultsmentioning
confidence: 83%
“…In addition to biological activities, the photophysical properties of chalcone derivatives have received much attention in studies such as nonlinear optics (NLO), photorefractive polymers, fluorescent probes for the detection of metal ions and organic luminescent as well as semiconducting device applications (Fayed, 2006;Wei et al, 2011;Si et al, 2011;Teo et al, 2017;Kwong et al, 2017;Karuppusamy et al, 2017;Nohut Maşlakcı et al, 2018). Also, bis-chalcones are an interesting class of compounds because of their use as precursors to potentially bioactive and functional compounds (Xu et al, 2001;Bukhari et al, 2013;Ritter et al, 2014;Albuquerque et al, 2014;Tala-Tapeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that a higher applied voltage increased the net charge experienced by the jet, resulting in enhanced fiber drawing to narrow diameters 39 . Meanwhile, the solvent volatilized quickly in electrospun processing, the appropriate parameters of polymer concentration, applied potential and, working distance are critical factors for optimized nanofibers 39,55 . SEM results for the nanofibers produced from multi‐block copolymers solution are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…We used bis‐chalcone derivatives in the synthesis of these compounds (Scheme 1). Bis‐chalcones were synthesized according to our procedure by the condensation of cyclohexanone with aromatic aldehydes [75] . By reacting 1,4‐Michael addition of bis‐chalcones with thiophenol, we were able to synthesize bis‐sulfides ( 5 a – i ) using our previous methods [56] .…”
Section: Methodsmentioning
confidence: 99%
“…Bischalcones were synthesized according to our procedure by the condensation of cyclohexanone with aromatic aldehydes. [75] By reacting 1,4-Michael addition of bis-chalcones with thiophenol, we were able to synthesize bis-sulfides (5 a-i) using our previous methods. [56] At room temperature and under straightforward reaction conditions, bis-sulfides (5 a-i) were changed into bissulfones (6 a-i) by the employment of the oxidant meta-chloroperbenzoic acid (m-CPBA) (Scheme 1).…”
Section: Chemistryselectmentioning
confidence: 99%